2014
DOI: 10.1007/s10531-014-0810-7
|View full text |Cite
|
Sign up to set email alerts
|

Using a citizen science program to monitor coral reef biodiversity through space and time

Abstract: Coral reefs are the most biodiverse ecosystems of the ocean and they provide notable ecosystem services. Large-scale monitoring is necessary to understand the effects of anthropogenic threats and environmental change on coral reef habitats and citizen science programs can support this effort. Seventy-two marine taxa found in the Red Sea were surveyed by non-specialist volunteers during their regular recreational dives, using SCUBA Tourism for the Environment (STE) questionnaires. Over a period of 4-years, 7,12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 36 publications
2
41
2
6
Order By: Relevance
“…Dive duration in our study for recreational divers (47.3 ± 36.8 min) is slightly lower than reported for Philippines (56 ± 6.4 min; Vianna et al, 2014), Florida (54.2 min; Camp and Fraser, 2012), or in the Red Sea at Sharm el Sheik (48.6 min; Branchini et al, 2015), and more similar to that found in the Mediterranean Sea (44-48 min;Terrón-Sigler et al, 2016). The shorter dive time in our study might be explained by the comparatively low water temperature in the Humboldt Current System (Thiel et al, 2007), which naturally reduces the amount of time divers are able to spend in the water (Stang and Wiener, 1970).…”
Section: Characterization Of Diverscontrasting
confidence: 75%
“…Dive duration in our study for recreational divers (47.3 ± 36.8 min) is slightly lower than reported for Philippines (56 ± 6.4 min; Vianna et al, 2014), Florida (54.2 min; Camp and Fraser, 2012), or in the Red Sea at Sharm el Sheik (48.6 min; Branchini et al, 2015), and more similar to that found in the Mediterranean Sea (44-48 min;Terrón-Sigler et al, 2016). The shorter dive time in our study might be explained by the comparatively low water temperature in the Humboldt Current System (Thiel et al, 2007), which naturally reduces the amount of time divers are able to spend in the water (Stang and Wiener, 1970).…”
Section: Characterization Of Diverscontrasting
confidence: 75%
“…Despite some background experience being required in these instances for safety, none of the reviewed projects required participants to have any educational background, as they become trained and therefore specialists in the task required (Hobson 2000). Furthermore, some projects allow participant development to a level whereby they can become project organizers, coordinators, or even lead authors in scientific publications and/or identification guides (see Bowen et al 2011 for an example of an identification guide authored by citizen scientists). An example includes Seasearch (available at www.seasearch.org.uk) that coordinates general surveys that all participants may undertake, as well as a 'surveyor' level survey for participants that undertake advanced training, and 'specialist projects' created by marine biology experts and experienced volunteers.…”
Section: Participant Recruitmentmentioning
confidence: 99%
“…Experience from the field trials and past CS projects showed that knowledge exchange between citizen scientists and researchers promotes trust and facilitates application of marine conservation schemes (Arvanitidis et al 2011, Thiel et al 2014). Participation to monitoring CS projects can itself have a positive effect on recreational participants’ knowledge level and environmental awareness (Branchini et al 2014). Establishing communication with users is also important for the optimization of the protocol and reporting of possible bugs in the website.…”
Section: Discussionmentioning
confidence: 99%
“…Although a plethora of CS projects deal with tropical coral reefs (e.g. Hodgson 2001, Marshall et al 2012, Branchini et al 2014) at a global scale, none has focused on their Mediterranean counterparts.…”
Section: Introductionmentioning
confidence: 99%